Nucleotide polymorphism of sucrose synthase (susy) from kelampayan (neolamarckia cadamba) - Chong, Hui Nei (University Malaysia Sarawak (UNIMAS), 2013)
Neolamarckia cadamba has high commercial value as its timber used as raw materials for production of plywood, pulp and paper, boxes and crates, light construction, dug-out canoes and furniture. Sucrose synthase (SuSy) catalyzes reversible formation of sucrose (Suc) and uridine diphosphate (UDP) into fructose (fru) and UDP-glucose (UDPG). UDPG is a major glycosyl donor for biosynthesis of cellulose, callose and starch. Single nucleotide polymorphism (SNP) is an important marker for selective breeding in the selection of desirable traits without growing plant until mature to observe phenotypic traits. The aim of this study was to identify the presence of SNP(s) in SuSy partial genomic sequence of Kelampayan. Targeted SuSy sequences were amplified by polymerase chain reaction (PCR). The ~800bp of SuSy partial genomic sequences was subjected to BLASTn analysis to search for sequence homology in NCBI. Sequences were then aligned by using CLC Sequence Viewer 6 software to identify SNP(s). There were 37 SNPs and 2 InDel polymorphisms detected in partial sequences of sucrose synthase.